Plasma sphingomyelin and longitudinal change in emphysema on computed tomography. The MESA Lung study - Ahmed, Firas S. (2014)
CONTEXT: Ceramide causes endothelial apoptosis and emphysema-like changes in animal models. OBJECTIVES: Test if plasma sphingomyelin, a major precursor of ceramide, would predict longitudinal increase in the percentage of emphysema-like lung on computed tomography (CT). MATERIALS AND METHODS: 3,840 participants had their plasma sphingomyelin measured at baseline examination and their pulmonary emphysema measured on cardiac CT scans at baseline and on follow-up visits. Mixed effects models were used to adjust for potential confounders. RESULTS: one standard deviation increase in sphingomyelin predicted a 0.12 % per year (95% CI: 0.02 to 0.22; p = 0.019) greater increase of percent emphysema. DISCUSSION AND CONCLUSION: Higher plasma levels of sphingomyelin predicted greater annual increase in quantitatively measured percent emphysema.